Antioxidant Intervention Against Microplastic Hazards - Zhihua Wang; Yunting Wang; Jian Zhang; Guoquan Feng; Shuhan Miao; Rongzhu Lu; Xinyu Tian; Yang Ye (Antioxidants, 2025)
Microplastic pollution (<5 mm) poses a serious threat to the environment and human health, inducing cellular stress damage in organisms (especially through oxidative stress). The damage results from excessive reactive oxygen species and impaired defense mechanisms, affecting energy production, organelles, and triggering inflammation. Antioxidants (such as vitamin C, curcumin, and quercetin) reduce stress markers and inflammation by neutralizing harmful molecules, activating protective pathways, and regulating autophagy, providing potential protection. However, practical applications face challenges such as low absorption rates, large individual variations, and unclear long-term safety. Research needs to delve into the molecular interaction mechanisms, develop effective delivery systems for antioxidant combinations, and formulate evidence-based strategies. Addressing the complexity of microplastics (size, shape, additives) and their cross-ecosystem impacts requires multidisciplinary collaboration. This review explores the oxidative stress mechanisms induced by microplastics, assesses the potential and limitations of antioxidant interventions, and provides a basis for environmental health risk management.